2012
DOI: 10.1002/cncr.27406
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal anti‐inflammatory drugs and the risk of skin cancer

Abstract: BACKGROUND: Nonsteroidal anti-inflammatory drugs (NSAIDs) may prevent the development of cancer by inhibiting cyclooxygenase (COX) enzymes, which are involved in carcinogenesis. Therefore, the authors of this report examined the association between NSAID use and the risk of squamous cell carcinoma (SCC), basal cell carcinoma (BCC), and malignant melanoma (MM). METHODS: From 1991 through 2009, all incident cases of SCC (n ¼ 1974), BCC (n ¼ 13,316), and MM (n ¼ 3242) in northern Denmark were identified. Approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 37 publications
5
79
0
4
Order By: Relevance
“…After 49 duplicates were removed, 237 titles and abstracts were reviewed and 11 full articles were retrieved for review (Amari et al, 2011;Asgari et al, 2010;Butler et al, 2005;Clouser et al, 2009;Cook et al, 2005;Elmets et al, 2010;Grau et al, 2006;Jeter et al, 2012;Johannesdottir et al, 2012;Nunes et al, 2011;Torti et al, 2011). Two reports identified did not contain sufficient information to meet the inclusion criteria (Amari et al, 2011;Cook et al, 2005) since one reported an effect estimate for keratinocyte cancers collectively (Amari et al, 2011), and the second reported estimates for total cancer and some major cancers excluding SCC (Cook et al, 2005), leaving 9 studies providing detailed data for inclusion in the meta-analysis.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…After 49 duplicates were removed, 237 titles and abstracts were reviewed and 11 full articles were retrieved for review (Amari et al, 2011;Asgari et al, 2010;Butler et al, 2005;Clouser et al, 2009;Cook et al, 2005;Elmets et al, 2010;Grau et al, 2006;Jeter et al, 2012;Johannesdottir et al, 2012;Nunes et al, 2011;Torti et al, 2011). Two reports identified did not contain sufficient information to meet the inclusion criteria (Amari et al, 2011;Cook et al, 2005) since one reported an effect estimate for keratinocyte cancers collectively (Amari et al, 2011), and the second reported estimates for total cancer and some major cancers excluding SCC (Cook et al, 2005), leaving 9 studies providing detailed data for inclusion in the meta-analysis.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…[10,11] In recent years, there has been an increased interest in the antitumour activity of NSAIDs due to at least three reasons: (1) COX-2 is found to be overexpressed in many cancers thus making it an attractive therapeutic target for the prevention and treatment of a number of malignancies [11,12]; (2) chronic inflammation has been proved to play an important role in cancer development and progression [13,14]; (3) NSAIDs are used also by oncology patients and the 'relationships' between these drugs and cancer cells have to be better clarified. [15] Numerous studies have suggested that aspirin and/or other NSAIDs can be effective in the prevention and/or treatment of malignancies, such as cancers of the colon, [16] breast, [17,18] lung, [19] pancreas, [20] prostate, [21,22] ovarium, [23] squamous cell carcinoma and melanoma, [24] etc. Different NSAIDs have been reported to inhibit the growth and survival of cell lines established from a wide variety of cancers, including gastric cancer, [25,26] cancers of the colon, [27] lung, [28] urinary bladder, [29] osteosarcoma, [30] etc.…”
Section: Introductionmentioning
confidence: 99%
“…A recent population-based study suggested that NSAIDs may decrease human SCC risk (8). Both indomethacin (an NSAID) and celecoxib (a COX-2 selective inhibitor), delay appearance of UVB-induced skin tumors on SKH-1 mice.…”
Section: Introductionmentioning
confidence: 99%